Enhancement of Voltage Profile in the Distribution system by Reconfiguring with DG placement using Equilibrium Optimizer - Muqthiar Ali Shaik; Padma Lalitha Mareddy; Visali N. (Alexandria Engineering Journal, 2022)
As the load steadily rises in a distribution system (DS), electrical power generation is improved. Inserting Distributed Generation (DG) unit in a DS has benefits such as enhancement in voltage profile and decreased power losses. In combination with optimal size, these advantages can be obtained to inject DG in the optimal location. Reconfiguration is another framework for optimizing the voltage profile and reduction of energy loss. Furthermore, reconfiguring the distribution network and installing the DG would ultimately improve system efficiency, which is undoubtedly challenging task. In this paper, equilibrium optimizer (EO) is explored to find out how to reconfigure the distribution network and how best DG can be positioned. For the IEEE-33 bus. Reliability Analysis is also done. The suggested method is implemented in MATLAB R2020A platform software. Outcomes of the suggested Technique based on the EO is compared with the existing techniques. There is Substantial improvement in voltage profile in addition to the decline in loss of power and reliability indexes (EENS, SAIFI, and SAIDI) for different cases of System with DG placement and System.